Effect of Magnetized Water on Histological Structure of Heart, Lung and Spleen of Albino Rats - Al-Saffar, Sura F; Amer, Nusaibah; Zaki, Lualuaa S; Faris, Ali S; Imran, Natheer J; Nadhim, Zainab F; Jaafar, Raed I (Al-Nahrain Journal of Science, 2013)
Abstract: The aim of the study was to investigate the effect of magnetized water on the histological structure of heart, lung and spleen. For this purpose, twenty five albino rats were divided into five equal groups, the first group was considered as control group. The other groups were given magnetized water with intensity of 250, 750, 1000, 1500 gause every day for 30 days. Then the animals were sacrificed and the histological change on heart, lung and spleen was studied. Histopathology of heart in rats treated with magnetic water with intensity of 250, 750, 1000, 1500 gause showed no clear pathological lesion. Lung section of rats treated with 250 gause of magnetic water showed no pathological lesion, while lung section belongs to rats group given magnetic water with intensity of 750, 1000 gause showed hyperplasia of lymphoid tissue in the wall of bronchiole and thickening to the wall alveoli, in addition the lung section belongs to magnetic water with intensity of 1500 agues treated rats showed thickening in alveolar wall. Spleen tissue belongs to magnetic water with intensity of 250 gause treated rats showed hyperplasia of the white pulp, while spleen tissue belongs to magnetic water with intensity of 750 gause treated rats showed a marked hyperplasia of the lymphoid tissue in the periarterial sheath. Also, spleen tissue belongs to magnetic water with intensity of 1000 gause treated rats showed amyloid like substance deposition around the white pulp. Necrotic area of lymphoid tissue was observed in the spleen tissue belongs to rat groups given magnetic water with intensity of 1500 gause